A model for a low risk prenatal control - Ricardo Ortiz Serrano; Mónica Andrea Beltrán Avendaño (MedUNAB, 2005)
A prenatal control is a very important tool, in order to detect, during pregnancy, all the potential risk factors, that the mother may suffer. Some of them are preventable or even treatable, in order to have a healthy mother, as well as a healthy child. By doing this we may keep a morbility and mortality rates, as well as perinatal complications, as low as possible. Those are the indicators for maternal-child health that are routinely measured in both, developed and developing Countries.We present a model of Prenatal Attention, adjusted to Colombiansocial security, which may restrict medicines, laboratory exams andthe like. This model may allow the physician in charge of prenatalcare to attend two patients with the same cost of one patient, according to the parameters implemented by the Colombian SocialWalfare Secretary.